Access to Care Limits Lung Cancer Screening Eligibility in an Urban Safety Net Hospital - Krista R. Dollar; Bradley S. Neutel; David W. Hsia (SAGE Publishing, 2022)
Purpose: Lung cancer screening (LCS) results in earlier detection of malignancy and decreases mortality but requires access to care to benefit. We assessed factors associated with timing of lung cancer diagnosis in the absence of systematic LCS in an urban safety net hospital. Patients and Methods: Retrospective chart review was performed of patients with pathologic diagnosis and/or staging of lung cancer at our institution between 2015 and 2018. Patient socio-demographics, disease characteristics, factors associated with access to medical care, and time point and process by which the patient accessed care were collected and analyzed. Results: In total, 223 patients were identified with median age of 63 years and 57.8% male predominance. Racial distribution was 22.9%, 20.2%, 17.1%, and 9.4% for Black, White, Asian, and Hispanic, respectively. Stage at diagnosis was 8.1%, 4.5%, 17.0%, and 60.5% for stages I, II, III, and IV, respectively. Medicaid (59.6%) and Medicare/Medicaid (17.1%) were the most common insurance types, while 16.1% had no insurance. A majority (54.3%) had no established primary care provider (PCP), and only 17.9% had an in-network PCP. Patients without PCPs were more likely to have diagnostic evaluation initiated from Emergency Department or Urgent Care settings (95.0% vs 50.1%, P  < .01) and present with later stage disease (92.7% vs 77.8%, P  < .01). Of the 83 patients that met age and smoking history LCS criteria, only 33.7% (12.6% of total) also had an in-network PCP. Conclusion: Absence of established PCPs is associated with later stage presentation of lung cancer and may limit system- level benefits of LCS implementation.